Prevalence and associated risk factors of cervical cancer among women in a Nigerian cohort - Timothy Aghogho Ehwarieme; Christiana I. Elusoji; Christie A. Enuku (Advances in Biomedical and Health Sciences)
Background: Cervical cancer is the fourth most common cancer in women worldwide. This study examined the prevalence of cervical cancer and associated factors among patients in a tertiary health facility in Edo state in Nigeria. Methods: A retrospective descriptive cross-sectional survey design was adopted including 3654 female patients who visited the oncology unit between 2016 and 2021. Their clinical files were selected through purposive sampling, and a validated checklist was used as instrument for data collection. Data analyses included descriptive and inferential statistics and multiple logistics regression. Results: Cervical cancer prevalence was highest in 2021 (10.8%). Oral contraceptives (23.8%), immunosuppression (19.3%), the number of sexual partners (8.3%), lack of human papillomavirus (HPV) vaccination (18.8%), diabetes (13.3%), and cardiovascular diseases (9.4%) were among the factors associated cervical cancer. A significant association (P = 0.000) was observed between risk factors and the clinical outcomes of cervical cancer. Women aged 30–59 were 25% more likely (odds ratio [OR] =1.25; 95% confidence interval [CI] = 0.55–2.86) to survive compared to those aged 60 and above. Women with only secondary education were also less likely (OR = 0.45; 95% CI = 0.21–0.99) to survive compared to those with tertiary education. Finally, multiparous women were less likely to survive compared to nulliparous women (OR = 0.30; 95% CI = 0.005–1.79). Conclusion: These results underscore the rising prevalence of cervical cancer and its association with age, supporting advocacy for increased HPV vaccination efforts targeting young girls before sexual maturity, as well as catchup vaccinations for high-risk older women.